LEVERAGING ARTIFICIAL INTELLIGENCE (AI) FOR ORGANIZATIONAL COMMUNICATION AND OPERATIONAL PERFORMANCE: THE CASE OF BANK BRI - Agnita Yolanda; Neni Triastuti (Smart Education, 2026)
Abstract: This research aims to determine and analyze the role of AI in the BRI Medan North Sumatra working place. Advances in artificial intelligence (AI) technology have had a significant impact on banking sector operations, including at Bank Rakyat Indonesia (BRI). The implementation of AI at BRI plays a role in improving operational process efficiency, customer service quality, and supporting data-driven decision-making. AI technology is applied in various areas, including customer service through chatbots, creditworthiness analysis and risk management, fraud prevention and detection, and personalized banking products and services. The result indicated that AI's ability to process data quickly and accurately enables BRI to minimize operational errors, optimize costs, and increase customer satisfaction. However, the implementation of AI also faces several challenges, such as data security protection, human resource readiness, and regulatory compliance. Therefore, the use of AI at BRI needs to be accompanied by strengthened governance and improved human resource competency to maximize the benefits of this technology in a sustainable manner. Keywords: Artificial Intelligence, Organizational Communication, Operational Performance, Digital Transformation, Banking Sector . Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis peran AI di lingkungan kerja bank BRI Medan Sumatra Utara. Kemajuan teknologi kecerdasan buatan (Artificial Intelligence/AI) telah memberikan dampak yang signifikan terhadap operasional sektor perbankan, termasuk di Bank Rakyat Indonesia (BRI). Implementasi AI di BRI berperan dalam meningkatkan efisiensi proses operasional, mutu layanan kepada nasabah, serta mendukung pengambilan keputusan yang berbasis analisis data. Teknologi AI diterapkan pada berbagai bidang, antara lain layanan nasabah melalui chatbot, analisis kelayakan kredit dan pengelolaan risiko, pencegahan dan pendeteksian penipuan, serta personalisasi produk dan layanan perbankan. Hasil penelitian menunjukkan bahwa kemampuan AI dalam memproses data secara cepat dan akurat memungkinkan BRI untuk meminimalkan kesalahan operasional, mengoptimalkan biaya, dan meningkatkan tingkat kepuasan nasabah. Namun demikian, penerapan AI juga dihadapkan pada sejumlah tantangan, seperti perlindungan keamanan data, kesiapan sumber daya manusia, serta kepatuhan terhadap regulasi. Oleh karena itu, pemanfaatan AI di BRI perlu disertai dengan penguatan tata kelola dan peningkatan kompetensi sumber daya manusia agar manfaat teknologi ini dapat dimaksimalkan secara berkelanjutan. Kata Kunci: Kecerdasan Buatan, Komunikasi Organisasi, Kinerja Operasional, Transformasi Digital, Sektor Perbankan